2021
DOI: 10.1371/journal.pgen.1009376
|View full text |Cite
|
Sign up to set email alerts
|

Histone modification dynamics at H3K27 are associated with altered transcription of in planta induced genes in Magnaporthe oryzae

Abstract: Transcriptional dynamic in response to environmental and developmental cues are fundamental to biology, yet many mechanistic aspects are poorly understood. One such example is fungal plant pathogens, which use secreted proteins and small molecules, termed effectors, to suppress host immunity and promote colonization. Effectors are highly expressed in planta but remain transcriptionally repressed ex planta, but our mechanistic understanding of these transcriptional dynamics remains limited. We tested the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 86 publications
7
74
0
Order By: Relevance
“…More importantly, we proved the PRC2 is exactly regulated by the MAP kinase Pmk1, which finely revealed Pmk1-downstream regulatory mechanism and PRC2 upstream regulatory mechanism. Together with the previous study by Zhang et al, (26), our study provides strong evidence that PRC2-mediated H3K27me3 is critical for modulating gene expression for biotrophic growth in M. oryzae.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…More importantly, we proved the PRC2 is exactly regulated by the MAP kinase Pmk1, which finely revealed Pmk1-downstream regulatory mechanism and PRC2 upstream regulatory mechanism. Together with the previous study by Zhang et al, (26), our study provides strong evidence that PRC2-mediated H3K27me3 is critical for modulating gene expression for biotrophic growth in M. oryzae.…”
Section: Introductionsupporting
confidence: 86%
“…In these studies, it has been shown that H3K27me3 correlates with gene silencing and plays a role in development, pathogenicity, and transcriptional regulation of secondary metabolite gene clusters (17,19). Recently, Functions of PRC2 was also revealed in M. oryzae, which indicated that PRC2-mediated H3K27me3 contributes to regulation of genes important during host infection, especially the effector proteins (26). However, it is far more unclear what's the role of PRC2 complex during fungi-plant interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal cultures were maintained under light at 25 °C on OTA to observe mycelial color change. For high-molecular-weight DNA extraction and protoplast preparation, related mycelial plugs for different strains from OTA were cultured in liquid CM at 28°C, 120rpm for 3-4 days as described before (50). In vitro crRNA synthesis and LbCas12a RNP assembly Oligos including T7 promoter (taatacgactcactatagg), LbCas12a direct repeat (taatttctactaagtgtagat), and 23-nt target sequences (Supplementary Table 2) were annealed and amplified to make the DNA template for in vitro RNA synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…2h). Additionally, to rule out that our observations are dependent on the HYG donor DNA and hygromycin selection, we performed the same experiments with a different donor DNA sequence coding for resistance to the drug G418 (Geneticin) (50). We again recovered transformants with the buff mutant phenotype and found that 70% (14/20) were PCR negative and 25% (5/20) had PCR amplification that suggested a simple insertion.…”
Section: Extended Homologous Sequence Is Not Required For Donor Dna Insertion At the Cas12a Double-strand Break Sitementioning
confidence: 99%